Evaluating Strategies to Reduce Ruminal Protozoa and Their Impacts on Nutrient Utilization and Animal Performance in Ruminants – A Meta-Analysis - Dai, Xiaoxia; Faciola, Antonio P. (Frontiers in Microbiology, 2019)
Several studies have evaluated the effects of complete or partial ruminal protozoa (RP) inhibition; however, to this date, no practical suppressant has been identified and used in large scale. This meta-analysis quantitatively evaluates the effectiveness of multiple strategies on inhibiting RP numbers and their influence on ruminal fermentation and animal performance. This study compared 66 peer-reviewed articles (16 manuscripts for complete and 50 manuscripts for partial RP inhibition that used supplemental phytochemicals and lipids, published from 2000 to 2018, to inhibit RP in vivo. Data were structured to allow a meta-analytical evaluation of differences in response to different treatments (complete RP inhibition, phytochemicals, and lipids). Data were analyzed using mixed models with the random effect of experiment and weighted by the inverse of pooled standard error of the mean (SEM) squared. Supplemental phytochemicals and LCFA had no effects on inhibiting RP numbers; however, supplemental MCFA had a potent antiprotozoal effect. Both complete and partial RP (supplemental phytochemicals and lipids) inhibition decreased methane production, total tract digestibility of OM and NDF, and ruminal NH3-N concentration and increased propionate molar proportion. Methane production, molar proportions of acetate and propionate, total tract NDF digestibility were affected by the interaction of treatment (supplemental phytochemicals and lipids) and RP numbers. Supplemental phytochemicals and lipids can be effective in reducing methane production when RP numbers is below 7 Log10 cells/mL, especially by supplemental saponins, tannins, and MCFA. In terms of animal performance, supplemental tannins could be recommended to control methane emissions without affecting animal performance. However, their negative effects on total tract digestibility could be a drawback when feeding tannins to ruminants. The negative effects of supplemental lipids on milk fat composition should be considered when feeding lipids to ruminants. In conclusion, ruminal protozoa play important roles on methanogenesis, fiber digestion, and ruminal NH3-N concentration, regardless of experimental diets and conditions; supplemental phytochemicals and lipids can be effective on reducing methane production when RP numbers is below 7 Log10 cells/mL. Among these partial RP inhibition strategies, supplemental tannins could be recommended to control methane production.